STYLOSANTHES CALCICOLA SMALL (FABACEAE), NEW DISTRIBUTIONAL RECORD FOR ASIA - Bhellum, B. L. (Annali di Botanica, 2018)
The paper deals with a new distributional record of Stylosanthes calcicola, a naturalised taxon for Asia. Taxonomic account of the species, description, and photographs are provided to facilitate its identity. The species is distinguished from other species of Stylosanthes, based on the almost straight beak of lomentum.